Taxonomy and distribution of Glenea beesoni Heller, 1926 (Coleoptera: Cerambycidae: Lamiinae: Saperdini) from Indian Himalayas. (3rd July 2018) - Lin, Mei-Ying; Dar, Mudasir Ahmad; Akbar, Shahid Ali
Abstract: The species Glenea beesoni Heller, 1926 is redescribed with genitalia morphology and Walnut plant ( Juglans regia Linnaeus of the family Juglandaceae) is confirmed to be the host plant of this species. Distribution map, habitus and genitalia pictures are provided.